Methyltransferase‐like 17 physically and functionally interacts with estrogen receptors. Issue 11 (21st October 2015) - Du, Peiyun; Yuan, Bin; Cao, Jia; Zhao, Jing; Ding, Lihua; Chen, Lihan; Ying, Sunyang; Jiang, Lina; Lin, Jiajia; Xu, Xiaojie; Cheng, Long; Ye, Qinong
Abstract: Estrogen exerts its physiological and pathological functions through two estrogen receptors (ERs), ERα and ERβ, which act as transcription factors. Coregulators, including coactivators and corepressors, have been shown to be crucial for regulation of ER transcriptional activity. Although many coregulators have been identified to regulate activities of ERs, novel coregulators are still needed to be investigated. Here, we show that human methyltransferase‐like 17 (METTL17), whose function is unknown, physically interacts with ERα and ERβ, and functionally acts as a coactivator for ERs. METTL17 interacts with ER in vitro and in yeast and mammalian cells. Activation function‐1 (AF1) and AF2 domains of ERs are responsible for the interaction between METTL17 and ERs. Knockdown of METTL17 reduces transcriptional activities of ERα and ERβ in breast cancer cells, whereas METTL17 overexpression increases ERα and ERβ transcriptional activities. Inhibition of METTL17 expression decreases mRNA and protein levels of ER target genes, including PR, cathepsin D, and pS2. Moreover, METTL17 knockdown reduces breast cancer cell growth. These results indicate that METTL17 is a novel coactivator of ERs and may play a role in breast tumorigenesis. © 2015 IUBMB Life, 67(11):861–868, 2015